Pengembangan Model Pembelajaran MIDHY (Model Video Based Learning with Virtual Laboratory) - Karmila, Mila; Bahri, Arsad (Universitas Negeri Makassar, 2022)
Abstract. This research was carried out using a literature review which aims to produce the development of a learning model that is expected to be one of the fun learning models that can form positive characters for students, improve science process skills, understanding concepts and be a solution for schools that have problems. on the lack of laboratory facilities and limited practical activities during the current Covid-19 pandemic. The model development in question is the development of a video-based learning with virtual laboratory (MIDHY) learning model. The development of the learning model in this paper adapts Video Based Learning media and Virtual Laboratory media as well as the application of the STAD (Student Teams Achievement Division) type learning model so that it gives birth to the MIDHY learning model with the syntax; 1). Motivation and material giving, 2). Group division, 3). Guide V-lab, 4). Presentation and Strengthening, 5). Synthesis and appreciation. The application of this model is accompanied by the use of virtual lab applications such as the Ministry of Education and Culture virtual lab, Olabs, Labster and several other virtual lab applications that support virtual practicum activities.Keywords: MIDHY learning model, video based learning, virtual laboratory, constructivism, STAD, concept understanding, science process skills, character education.